Statistical methods for transverse beam position diagnostics with higher order modes in third harmonic 3.9 GHz superconducting accelerating cavities at FLASH - Zhang, Pei; Baboi, Nicoleta; Jones, Roger M. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2014)
Beam-excited higher order modes (HOMs) can be used to provide beam diagnostics. Here we focus on 3.9 GHz superconducting accelerating cavities. In particular we study dipole mode excitation and its application to beam position determinations. In order to extract beam position information, linear regression can be used. Due to a large number of sampling points in the waveforms, statistical methods are used to effectively reduce the dimension of the system, such as singular value decomposition (SVD) and k-means clustering. These are compared with the direct linear regression (DLR) on the entire waveforms. A cross-validation technique is used to study the sample independent precisions of the position predictions given by these three methods. A RMS prediction error in the beam position of approximately 50 mu m mu m can be achieved by DLR and SVD, while k-means clustering suggests 70 mu m mu m.